Structural Study of Plasticized Carboxy Methylcellulose Based Solid Biopolymer Electrolyte - M.I.N. Isa; M.N. Chai (Trans Tech Publication, 2024)
Carboxyl methylcellulose (CMC) doped with oleic acid (OA) and plasticized with glycerol was able to be produced into solid biopolymer electrolytes using the solution cast technique. The CMC-OA-glycerol solid polymer electrolyte obtained the highest conductivity of 1.64 x 10-4 S cm-1 at room temperature for sample Gly 40 wt. %. Within the temperature range investigated, the conductivity– temperature relationship of the biopolymer electrolytes is characteristically Arrhenius behaviour, suggesting that the conductivity is thermally assisted. Fourier Transform Infrared studies was carried out to determine the dissociation of free protons (H+) from the carboxyl group (–COOH) of glycerol.